2014
DOI: 10.5194/acp-14-12745-2014
|View full text |Cite
|
Sign up to set email alerts
|

Fast transport from Southeast Asia boundary layer sources to northern Europe: rapid uplift in typhoons and eastward eddy shedding of the Asian monsoon anticyclone

Abstract: Abstract. Enhanced tropospheric trace gases such as CO, CH4 and H2O and reduced stratospheric O3 were measured in situ in the lowermost stratosphere over northern Europe on 26 September 2012 during the TACTS aircraft campaign. The measurements indicate that these air masses clearly differ from the stratospheric background. The calculation of 40-day backward trajectories with the trajectory module of the CLaMS model shows that these air masses are affected by the Asian monsoon anticyclone. Some air masses origi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
159
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(175 citation statements)
references
References 62 publications
15
159
1
Order By: Relevance
“…After a few months, however, the two distributions of anticyclone edge and core air align (Fig. 4d, f), showing that, in the long term, air masses ascending in the anticyclone core and air masses injected into the anticyclone edge (e.g., by typhoons; see Vogel et al, 2014) follow the same transport pathways. The higher fraction of air from the anticyclone edge compared to the core is likely a result of the larger area of the edge region.…”
Section: Discussionmentioning
confidence: 99%
“…After a few months, however, the two distributions of anticyclone edge and core air align (Fig. 4d, f), showing that, in the long term, air masses ascending in the anticyclone core and air masses injected into the anticyclone edge (e.g., by typhoons; see Vogel et al, 2014) follow the same transport pathways. The higher fraction of air from the anticyclone edge compared to the core is likely a result of the larger area of the edge region.…”
Section: Discussionmentioning
confidence: 99%
“…The identification and the relative importance of different transport pathways of tropospheric source gases found within the Asian monsoon anticyclone into the lower stratosphere are the subject of a longstanding debate (Dethof et al, 1999;Park et al, 2004;Randel et al, 2010;Bian et al, 2012;Bourassa et al, 2012;Ploeger et al, 2013;Fairlie et al, 2014;Fromm et al, 2014;Uma et al, 2014;Vogel et al, 2014Vogel et al, , 2015Garny and Randel, 2016;Tissier and Legras, 2016;Orbe et al, 2015). The influence of these different transport pathways on the chemical composition of the extratropical upper troposphere and lower stratosphere (ExUTLS) is important because changes in ozone and water vapor in the ExUTLS have a significant impact on surface climate, even if the perturbation is relatively small.…”
Section: Introductionmentioning
confidence: 99%
“…The O 3 distribution in the troposphere is strongly influenced by dynamical processes, as well as by the regional chemical sources and sinks of O 3 . Previous studies (e.g., Park et al, 2007;Worden et al, 2009;Vogel et al, 2014) have demonstrated that rapid convective transport associated with the Asian monsoon anticyclone can result in significant enhancement of O 3 abundance over Asia, northern Africa and Europe. The stratosphere-troposphere exchange of O 3 also has important effects on the distribution of tropospheric O 3 (e.g., Barth et al, 2012;Neu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2009) indicated that the enhancement of free tropospheric O 3 over the Middle East is mainly due to the influence of the Arabian anticyclone in the middle troposphere, which traps O 3 that is produced locally as well as O 3 and its precursors that are transported from rest of Asia. Recent studies (Ricaud et al, 2014;Vogel et al, 2014) demonstrated that the Asian monsoon anticyclone provides an effective pathway to redistribute Asian pollutants globally. An improved understanding about the mechanism of the summertime enhancement of free tropospheric O 3 over the Middle East is thus important as it will provide critical information about the sources and variation of tropospheric O 3 in the Northern Hemisphere.…”
Section: Introductionmentioning
confidence: 99%